PENGARUH STRUKTUR AKTIVA DAN UKURAN PERUSAHAAN TERHADAP STRUKTUR MODAL PADA PERUSAHAAN PROPERTY DAN REAL ESTATE YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2012-2016 - Umi Narimawati; Pradhana Aji Prasusti (Jurnal Ilmu Keuangan dan Perbankan (JIKA), 2016)
ABSTRACTThis study was conducted to examine the effect of Asset Structure variable and the Size of the Company's capital structure to the Property and Real Estate Companies listed on the Indonesian Stock Exchange from 2012-2016. The focus of this study is to analyze the influence of these variables on Capital Structure . The method used in this research is descriptive verificative method with quantitative approach. Purposive sampling was used in this study with the following criteria: (1) The Companies that are engaged in property and real estate sector listed on the Stock Exchange from 2012-2016, (2) The Companies that reported their financial statements in a row on the Indonesian Stock Exchange in the period 2012-2016, (3) The Companies that have the data completeness according to the examined variables in this study. The samples in this study are6 of 49 property and real estate companies listed on the Indonesian Stock Exchange. This study uses multiple regression analysis and hypothesis testing using t-statistics to test the partial regression coefficient and f-statistic to examine the effect together with a significance level of 5%. Furthermore, it also made the classic assumption test including normality test, multicollinearity test, heteroscedasticity test and autocorrelation test.Statistical analysis shows a strong correlation between asset structure, company size and capital structure in the Property and Real Estate companies. The structure and the size of the company's assets have a significant effect on the capital structure. The conclusion of this study is simultaneously the assets structure significantly influence capital structure, and also company’s size significantly influence the company's capital structure partially.Keywords: Activa Structure, Company Size, Capital Structure